Safety and Biological Activity of Rozibafusp alfa, a Bispecific Inhibitor of Inducible Costimulator Ligand and B Cell Activating Factor, in Patients With Rheumatoid Arthritis: Results of a Phase 1b, Randomized, Double‐Blind, Placebo‐Controlled, Multiple Ascending Dose Study - Lubna Abuqayyas; Laurence E. Cheng; Marcia Teixeira dos Santos; Barbara A. Sullivan; Norma Ruiz‐Santiago; Hui Wang; Yanchen Zhou; Vishala Chindalore; Stanley Cohen; Alan J. Kivitz; Maximilian G. Posch; Jane R. Parnes (ACR Open Rheumatology, 2022)
Objective To assess the safety and biological activity of rozibafusp alfa, a first‐in‐class bispecific antibody–peptide conjugate targeting inducible costimulator ligand (ICOSL) and B cell activating factor (BAFF), in patients with rheumatoid arthritis (RA). Methods This phase 1b, double‐blind, placebo‐controlled, multiple ascending dose study included 34 patients (18–75 years; 82.4% female) with active RA (Disease Activity Score of 28 joints–C‐reactive protein [DAS28‐CRP] >2.6, on stable methotrexate) randomized 3:1 to receive rozibafusp alfa (n = 26, in four ascending dose cohorts of 70, 140, 210, and 420 mg) or a placebo (n = 8) subcutaneously once every 2 weeks for 10 weeks (six total doses), with 24 weeks of follow‐up. The primary end point was the incidence of treatment‐emergent adverse events (TEAEs). Additional assessments included serum pharmacokinetics (PK), pharmacodynamics (PD), immunogenicity, and RA disease activity measures (DAS28‐CRP, Patient Global Assessment of Disease, and Physician Global Assessment of Disease). Results TEAEs occurred in 96.2% and 87.5% of patients receiving rozibafusp alfa and the placebo, respectively; most were mild or moderate in severity. Two (7.7%) patients treated with rozibafusp alfa reported serious TEAEs; none were considered treatment related. Multiple doses of rozibafusp alfa showed nonlinear PK (mean t1/2 = 4.6–9.5 days) and dose‐related, reversible PD (>90% ICOSL receptor occupancy in 210‐ and 420‐mg cohorts; reduction in naïve B cells and increase in memory B cells in all cohorts). Five (20%) patients developed anti–rozibafusp alfa antibodies, with no apparent impact on safety. RA disease activity showed greater numerical improvement from baseline with rozibafusp alfa versus the placebo in the 210‐ and 420‐mg cohorts. Conclusion Multiple ascending doses of rozibafusp alfa were well tolerated, with PK and PD reflecting dual ICOSL and BAFF blockade. Findings support further clinical evaluation of rozibafusp alfa in autoimmune disease.